Cooperation, competition, and risk attitudes: an intergenerational field and laboratory experiment - Gary Charness; Marie-Claire Villeval (Institute for the Study of Labor (IZA), 2007)
The population of most developed societies is 'graying'. As life expectancy increases and the large baby-boom generation approaches retirement age, this has critical consequences for maintaining a high standard of living and the sustainability of pension systems. In the light of these labor-force and social concerns, we consider experimentally the comparative behavior of juniors (under 30) and seniors (over 50) in both experiments conducted onsite with the employees of two large firms and in a conventional laboratory environment with students and retirees. Our results are compelling. First, seniors are not more risk-averse, as opposed to the conventional stereotype. Second, both juniors and seniors react to the competitiveness of the environment and there is no significant difference in performance in the real-effort task across the generations when they are competing. Third, seniors are typically more cooperative than juniors in a team-production game. Cooperation is highest in groups in which there is a mix of juniors and seniors, suggesting that there are indeed benefits in maintaining a work force with diversity in age. Overall, the implication is that it is beneficial to define additional short-term incentives near the end of the workers' career to motivate and to retain older workers. A secondary, but important, issue is the external validity of conventional laboratory experiments. In general we do not find strong differences in behavior between workers and non-workers, indicating that laboratory experiments may not be such a bad approximation for the field environment.
urn:nbn:de:101:1-20080425212
Keywords: 330; Gruppenentscheidung; Altersgruppe; Kooperation; Wettbewerb; Risikopräferenz; Arbeitsmarktdiskriminierung; Alternde Bevölkerung; Test; Feldforschung; Frankreich